Analisis Pengaruh Pemberian Kredit Dari Badan Kredit Kecamatan (BKK) Terhadap Pendapatan Pedagang Kecil Di Sukoharjo Tahun 2015 - PARAMUDITA, AISYAH PUTRI; , M.YAHYA, M.Si (2016)
The purpose of this study was to determine: 1) know the market is there any influence of credit on the income of small traders. 2) To know is there any influence weekly lending to small traders revenue. 3) To determine the effect of the provision is there any monthly credit against the income of small traders. 4) To determine the effect of the credit market is there, weekly, and monthly income of the small traders. This research is quantitative descriptive research by drawing conclusions through statistical analysis. The population in this study are small traders borrowers of capital in the District Credit Agency (BKK) in Sukoharjo, Central Java. Samples taken as many as are 40 people with random sampling. Necessary data obtained through questionnaires and documentation. The questionnaire previously tested and tested for validity and reliability were tested. Data analysis technique used is multiple linear regression analysis, F test, t-test, R2, and the relative contribution and effective. The results of the regression analysis obtained regression equation: Y = 5,590 + 0,480X1 + 0,334X2 + 0,240X3. The equation shows that the income of small traders affected by the credit market, weekly, and monthly. The conclusions drawn were: 1) "There is the influence of the market credit on the income of small traders" unacceptable. This is based on multiple linear regression analysis (t test) note that tcount> ttable, namely 7.504> 2.042 and the significance value <0.05, ie 0,000 effective contribution of 29.4%. 2) "There is a weekly credit effect on the income of small traders" unacceptable. This is based on multiple linear regression analysis (t test) note that tcount> ttable, namely 5.431> 2.042 and the significance value <0.05, ie 0,000 effective contribution of 21.1%. 3) "There is a monthly credit on the income effect of small traders" unacceptable. This is based on multiple linear regression analysis (t test) note that tcount> ttable, namely 3.086> 2.042 and the significance value <0.05, namely 0.004 with the effective contribution of 14%. 4) "There is the influence of the credit market, weekly, and monthly income of the small traders" unacceptable. This is based on multiple linear regression analysis of variance (F test) is known that F count> F table, ie 142.227> 3.320 and the significance value <0.05, namely 0.000. 5) The result of the coefficient of determination (R2) of 0.184 indicates that the influence of the credit market, weekly, and monthly basis together against small traders revenues amounted to 64.5%, while 35.5% is influenced by other variables not examined